Strength Structure Analysis of Main Gate Graving Dock Using Pontoons for Condition Repairs - Budianto, Budianto (UI Scholars Hub, 2018)
Main gate graving dock with pontoon type can certainly suffered some level of damage after a long period of operation. Many employments within the graving dock can delay the process repair of main gate. The main gate may not be opened, because employees are still working to ship fabrication process under sea waterline. For accommodate these interrelated conditions, the best solution with repair one side of the main gate with type pontoon and employees can still work ship fabrication process in graving dock conducted simultaneously. The repair process conditions must be required main gate structure that consists of only one part of the shell withstand the forces that occur, such as weight self and sea pressure. It must be considered with analysis of the strength structures of main gate graving dock with pontoon type. Finite element method can solve the problem of structural analysis using the element discretion approach to find a node or joint displacement and the forces that occur in structural repair conditions at main gate. The maximum bending stress value obtained during the main gate repair process is 153 mPa, and the allowable stress value is classified as 157 mPa. Since these conditions are approaching the allowable limit, the main gate needs to be given insert plates for reinforcement. Deformation is found to be 12 mm, and the deformation limit is 35 mm based on the rule's classification.